KEPEMIMPINAN KEPALA SEKOLAH DI ERA REVOLUSI INDUSTRI 4.0 DALAM MENINGKATKAN AKREDITASI SEKOLAH - Wulandari, Fitri; Febriansyah, Dwi; Salwa, Salwa; Sulaiman, Raden Muhamad (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2019)
The leader is the person who leads. While the leader is his position. In another sense, etymologically the term leadership comes from the basic word "lead" which means guidance or guidance. Brodjonegoro (2018) workers in all fields in the era of Industrial Revolution 4.0 are required to have digital skills, both technical and managerial workforce. In addition to the demand for appropriate skills, it turns out that social skills are also very much needed in working in the era of the Industrial Revolution 4.0. The results of studies in several developed countries indicate that there is an increasing need for analytical non-routine skills and interactive non-routine skills. While the need for routine cognitive skills, non-routine manuals, and manual routines has decreased. Ideal leadership is leadership that follows the demands of the 4.0 industrial revolution. leaders who follow technological developments leaders must have skills in influencing, encouraging, guiding, directing, and mobilizing others who have to do with the implementation and development of education and teaching in the industrial revolution era 4.0.